2019
DOI: 10.1021/acs.jproteome.9b00028
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic Profiling of Tyrosine Kinase Inhibitor-Resistant K562 Cells Suggests Metabolic Reprogramming To Promote Cell Survival

Abstract: Resistance to chemotherapy can occur through a wide variety of mechanisms. Resistance to tyrosine kinase inhibitors (TKIs) often arises from kinase mutations-however, "off-target" resistance occurs but is poorly understood. Previously, we established cell line resistance models for three TKIs used in chronic myeloid leukemia treatment, and found that resistance was not attributed entirely to failure of kinase inhibition. Here, we performed global, integrated proteomic and transcriptomic profiling of these cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 83 publications
5
11
0
Order By: Relevance
“…In this sense, we further determined that the expression of the majority of PPP enzymes and activity of the two main enzymes (G6PD and TKT) were upregulated in the TKI-resistant cells ( Figure 3 D–F), leading us to conclude that KU812 ImaR cells have enhanced both oxidative and non-oxidative PPP, probably because this cell line may require more ribose-5-P, which plays a vital role for nucleotide synthesis, and NADPH which is essential for fatty acid synthesis, redox homeostasis and ROS scavenging [ 36 ]. These results agree with the enhanced PPP also observed by Noel et al in K562 imatinib-resistant cells [ 32 ]. Furthermore, our results revealed that KU812 ImaR cells ensure an enhanced PPP flux thanks in part to the activation of glycogen synthesis and glycogenolysis, similarly to the results shown in a study performed with T-cells [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this sense, we further determined that the expression of the majority of PPP enzymes and activity of the two main enzymes (G6PD and TKT) were upregulated in the TKI-resistant cells ( Figure 3 D–F), leading us to conclude that KU812 ImaR cells have enhanced both oxidative and non-oxidative PPP, probably because this cell line may require more ribose-5-P, which plays a vital role for nucleotide synthesis, and NADPH which is essential for fatty acid synthesis, redox homeostasis and ROS scavenging [ 36 ]. These results agree with the enhanced PPP also observed by Noel et al in K562 imatinib-resistant cells [ 32 ]. Furthermore, our results revealed that KU812 ImaR cells ensure an enhanced PPP flux thanks in part to the activation of glycogen synthesis and glycogenolysis, similarly to the results shown in a study performed with T-cells [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our analyses support the fact that TKI-resistant cells became more glycolytic during the resistance development ( Figure 3 ) and unveil the rewiring of glucose usage to other pathways different from glycolysis such as PPP, glycogen synthesis and SGOC metabolism. This aligns with published data showing that CML cells have a preference for glycolytic degradation of glucose to lactate [ 16 , 32 ], as well as with long-term imatinib resistant cells which increase glycolysis and PPP, using glycolysis to an even higher degree than parental cells [ 32 ]. It is worth noting that the extracellular acidification rate, a measurement of excreted H + , did not change between parental and TKI-resistant cells even though lactate production was increased in the TKI-resistant cells.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of clinical TKI resistance is caused by mutations in the BCR-ABL gene 58 , and T315I mutation detected in all our JURL-MK1 and MOLM-7 TKIresistant variants (Figure 4) illustrates the importance of this gatekeeper mutation in the process. On the other hand, similarly to other laboratory findings 59,60 , resistant sub-lines derived from the K562 cell line did not develop any mutation in the BCR-ABL kinase domain. This fact, together with the lack of overactivation of P-CRKL (Figure 3) suggests a resistance mechanism independent of BCR-ABL in these cells.…”
Section: Discussionsupporting
confidence: 87%
“…The use of tyrosine kinase inhibitors (TKIs) as therapeutic agents for human myeloid leukemia has been shown to lead to resistance in patients due to a wide variety of off‐target mechanisms . After the treatment of sensitive or resistant chronic myeloid leukemia cell lines with three TKIs (imatinib, dasatinib, and nilotinib), whole transcriptome sequencing and SWATH‐based proteome analysis were used to discover off‐targets (CA1 and alpha‐synuclein) and biological pathways (oxidative stress responses, hypoxia conditions, and metabolic disruptions) related to TKI resistance . Consequently, identifying proteomic‐wide off‐targets for novel bioactive small molecules and/or existing drugs and the biological pathways involved will be pivotal in drug repositioning and developing effective and safe drugs.…”
Section: Summary and Future Directionsmentioning
confidence: 99%